CULTURAL CAPITAL AS AN ECONOMIC DRIVER THROUGH COMMUNITY-BASED TOURISM IN TOURISM VILLAGES, INDONESIA - Laily Hidayati Rosyidi (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This study analyzes the conversion of cultural capital of the Osing Tribe into an economic driver through Community-Based Tourism (CBT) in Kemiren Village, Banyuwangi. The focus is to examine how tangible cultural wealth (such as language, art, and architecture) and institutionalized (as Cultural Heritage and Superior Tourism Villages) is managed as sustainable economic assets. The goal is to uncover the mechanisms and impacts of cultural capital transformation in the community-based tourism value chain. With a qualitative approach to case studies, data is collected through in-depth interviews, observations, and document studies. The results of the study show that Pokdarwis and BUMDes play a strategic curatorial role in packaging cultural capital into an integrated experience package, creating an independent economic ecosystem and maintaining narrative authority in the hands of the community. This success is supported by participatory governance that strengthens cultural sustainability, social cohesion, and economic resilience. It is concluded that community-centered CBT and cultural sovereignty are an effective model for sustainable development, with the main challenge of maintaining a balance between commercialization and the integrity of cultural values.